On the Importance of the Microbiome and Pathobiome in Coral Health and Disease - Sweet, Michael J.; Bulling, Mark T. (Frontiers in Marine Science, 2017)
The term 'microbiome' was first coined in 1988 and given the definition of a characteristic microbial community occupying a reasonably well defined habitat which has distinct physio-chemical properties. A more recent term has also emerged, taking this one step further and focusing on diseases in host organisms. The 'pathobiome' breaks down the concept of ‘one pathogen = one disease’ and highlights the role of the microbiome, more specifically certain members within the microbiome, in causing pathogenesis. The development of next generation sequencing has allowed large data sets to be amassed describing the microbial communities of many organisms and the field of coral biology is no exception. However, the choices made in the analytical process and the interpretation of these data can significantly affect the outcome and the overall conclusions drawn. In this review we explore the implications of these difficulties, as well as highlighting analytical tools developed in other research fields which hold substantial potential in helping to develop a deeper understanding of the role of the microbiome in disease in corals. We also make the case that standardisation of methods will substantially improve the collective gain in knowledge across research groups. We hope this review acts as a guide to researchers exploring this field of microbiome and pathobiome in coral research and acts as a jumping off point for future studies.